Nonlinear dynamic analysis of two external excitations for the gear system using an original computational algorithm. (October 2020) - Liu, Fuhao; Zhang, Liang; Jiang, Hanjun; Zhang, Jielu
Highlights: A dynamic gear model is developed by incorporating two external excitations. An original computational algorithm is proposed with smarter time-step methods. The numerical advantages of the original computational algorithm are illustrated. The influence of two external excitations are systematically investigated. Abstract: In this work, a dynamic gear model has been developed by incorporating both the driving speed and the drag torque as external excitation sources. An original computational algorithm, with adaptive selection of the time-step method (for guaranteeing precision) and smarter time-step reduced method (for increasing efficiency), is proposed by defining a very small transition area between lubricant and solid contact. This algorithm can overcome the limitations of known prior research work and make sure an accurate determination of the time and position for lubricant/solid contact. Numerical results are presented to illustrate and quantify the influence of the external excitations, as well as the numerical advantages of the original computational algorithm in comparison with various Matlab solvers. The results presented in this study provide an understanding of the external excitations under which undesirable dynamic motion takes place and therefore serve as a useful source of reference for engineers in controlling such gear systems.